2005
DOI: 10.1081/dct-39731
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Fluorometric Method to Study Sulfur Mustard–Induced Apoptosis in Human Epidermal Keratinocytes Monolayer Microplate Culture

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…As shown in Figure 5, we found that CEES induced activation of caspase 3 was maximal after 12 hours of incubation, which is in agreement with other reports regarding CEES or HD toxicity in human skin cells [18,21,22]. Figure 6C and D, respectively).…”
Section: Cees(µm)supporting
confidence: 81%
“…As shown in Figure 5, we found that CEES induced activation of caspase 3 was maximal after 12 hours of incubation, which is in agreement with other reports regarding CEES or HD toxicity in human skin cells [18,21,22]. Figure 6C and D, respectively).…”
Section: Cees(µm)supporting
confidence: 81%
“…In terms of SM concentration and its cellular toxicity used for in vitro studies, Gentilhomme et al [19] showed that SM, bis(beta-chloroethyl) sulfide (BCES), at concentrations ranging from 5 to 500 mM did not affect cellular viability in human dermal fibroblasts in vitro. Ray et al also reported that SM at the concentrations more than 100 mM caused triggered apoptotic pathway, but SM less that 50 mM did not [20] in the same NHEK model we used in our experiments. The relatively strong eNOS expression did not change during wound healing regardless of SM exposure, indicating that NO production by eNOS is not directly related to inhibition of wound healing.…”
Section: Discussionmentioning
confidence: 51%
“…Recently, Fitsialos et al identified the proinflammatory cytokines or chemokines such as IL5RA, IL8, IL18, and LIF in NHEK response to scratching using a DNA microarray approach. Those soluble factors have been previously associated not only with wound healing using in vivo and in vitro models [20] and also shown to regulate iNOS expression [21].…”
Section: Discussionmentioning
confidence: 98%
“…Keratinocytes exposed to BFA undergo cell death via an apoptotic-necrotic continuum (Ray et al, 2005). CAPE itself is a known radiosensitizer (Lin et al, 2006) and inducer of apoptosis in a variety of cell lines (Chiao et al, 1995).…”
Section: Resultsmentioning
confidence: 99%